A comparative survey on the increased fracture resistance of amalgam restored teeth using three types of Glass Ionomer as adhesive liners - Shafiee F.; Borhan Haghighi Z (Tehran University of Medical Sciences, 2004)
Statement of Problem: Because dental amalgam does not adhere to tooth structure, using adhesive cements in amalgam-bonded restorations have been increased. Purpose: The goal of this in-vitro study was to compare the effects of three types of glass ionomer as adhesive liners as well as varnish liner in increasing fracture resistance of teeth restored with amalgam. Materials and Methods: Seventy extracted human maxillary premolars were selected and MOD cavities were prepared on them excluding ten intact teeth as positive control group and ten cavity prepared teeth without restoration as negative control group. All the prepared teeth were then restored with spherical amalgam (gs.80) with one of the following liners silver alloy glass ionomer liner, conventional glass ionomer liner, varnish liner, resin-modified glass ionomer and resin-modified glass ionomer with delayed light curing. The teeth were stored in 37C distilled water for 7 days and were then loaded under compressive strength using an Instron testing machine. The force required to fracture teeth were recorded and the data were analyzed statistically using ANOVA and Tukey HSD tests. Results: Statistically significant differences were observed in fracture resistance between restored and non-restored samples. Comparisons between groups attributed significant effects to resin-modified glass ionomer in increasing fracture resistance of amalgam restored teeth (P<0.05). In most specimens, one cusp was separated from tooth structure whereas amalgam remained bonded to the intact cusp. Conclusion: According to these findings, resin-modified glass ionomer put a statistically significant effect in fracture resistance of amalgam-restored teeth.